'A bit of bread and cheese': what people eat in revolutionary times. Issue 2 (3rd May 2020) - Arribas, Sonia
ABSTRACT: I analyse Kropotkin's The Conquest of Bread, focusing on the symbol of 'bread'. This allows me to offer a reading of it that is different from the way in which it is usually read – as a revolutionary programme anchored in the belief in scientific progress. In my view, we should rather take it as literature, the fruit of Kropotkin's imagination. I explain how 'bread' serves different functions: it is a rhetorical device; it is a link between the natural and the social; it serves as a representation of materiality as opposed to mere ideas; it conveys the satisfaction of needs; it represents the specific form of anarchism defended by Kropotkin; it serves him to argue against the political economy of his time; and it functions as the foundation of ethics. I also read the book backwards, starting from its last sentences, where Kropotkin denies that he is writing fiction. I take this as a Freudian negation, and argue that the book can only be read today as literature. Kropotkin himself acknowledges in several places that his own writing is being led not so much by the scientific method that he advocates, but by the free powers of the imagination.